2019
DOI: 10.1007/s12671-019-01115-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Mindful Parenting Mediate the Association between Maternal Anxiety during Pregnancy and Child Behavioral/Emotional Problems?

Abstract: Objectives Maternal anxiety during pregnancy is a risk factor for child behavioral/emotional problems. Knowledge about explanatory factors mediating this link is scarce. Maternal anxiety during pregnancy may be an indicator of adverse postnatal environmental conditions, including maternal anxiety and poor parenting, possibly affecting child behavior. This study investigated whether maternal anxiety and mindful parenting in early childhood mediate the association between maternal anxiety during pregnancy and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…For example, bolstering psychological flexibility has been shown to reduce work-related stress ( Wersebe, Lieb, Meyer, Hofer, & Gloster, 2018 ). Consistent with this, a growing number of studies have linked psychological flexibility in parents to more kind and compassionate family interactions (e.g., MacDonald, Hastings, & Fitzsimons, 2010 ; Wong, Mak, & Liao, 2016 ), more adaptive parenting practices (e.g., Burke & Moore, 2015 ; McCaffrey, Reitman, & Black, 2017 ; Moreira & Canavarro, 2017 ), and greater individual well-being for both children (e.g., Henrichs, van den Heuvel, Witteveen, Wilschut, & Van den Bergh, 2019 ) and for the parents themselves (e.g., Neff & Faso, 2015 ). To build on this work, the current study sought to apply this conceptual framework toward understanding the possible impact of COVID-19 on families during this worldwide crisis, positing that parental psychological flexibility might serve as a key source of resilience within families.…”
Section: Conceptual Frameworkmentioning
confidence: 84%
“…For example, bolstering psychological flexibility has been shown to reduce work-related stress ( Wersebe, Lieb, Meyer, Hofer, & Gloster, 2018 ). Consistent with this, a growing number of studies have linked psychological flexibility in parents to more kind and compassionate family interactions (e.g., MacDonald, Hastings, & Fitzsimons, 2010 ; Wong, Mak, & Liao, 2016 ), more adaptive parenting practices (e.g., Burke & Moore, 2015 ; McCaffrey, Reitman, & Black, 2017 ; Moreira & Canavarro, 2017 ), and greater individual well-being for both children (e.g., Henrichs, van den Heuvel, Witteveen, Wilschut, & Van den Bergh, 2019 ) and for the parents themselves (e.g., Neff & Faso, 2015 ). To build on this work, the current study sought to apply this conceptual framework toward understanding the possible impact of COVID-19 on families during this worldwide crisis, positing that parental psychological flexibility might serve as a key source of resilience within families.…”
Section: Conceptual Frameworkmentioning
confidence: 84%
“…Third, it is difficult to disentangle contributions of the postnatal environment to child sleep problems. It is known that prenatal stress may affect maternal parenting 66 , which, in turn, can contribute to child sleep problems. However, the fact that maternal prenatal stress was found to impact functional connectivity of the fetal brain suggests that biological mechanisms are, at least, partly at play.…”
Section: Discussionmentioning
confidence: 99%
“…Not only maternal postpartum mental health but also maternal mental health in the childhood period affects child emotional functioning. Previous studies observed that maternal anxiety and depression in (early) childhood are associated with child emotional and behavioral problems (35,36). Both the postpartum period and the early childhood period are mentally demanding periods in a woman's life.…”
Section: Introductionmentioning
confidence: 99%